Important aspects of the formation of a sense of patriotism in the layer of owners - Rakhmankulov Farhod (Periodica Journal, 2024)
This article discusses the philosophical content of the patriotic feeling. There has also been a reflection on the linguistic meaning of patriotism, on how important this feeling is in society, and on its positive impact on the layer of owners. The article also analyzes the activities of patriotic owners in the world, Uzbekistan
Keywords: Homeland; patriotism; sacrifice